Advances in Computer Communication and Computational Sciences Proceedings of IC4S 2018 - Bhatia, Sanjiv K.; Tiwari, Shailesh; Mishra, Krishn K.; Trivedi, Munesh C. (Advances in Intelligent Systems and Computing,, 2019)
This book includes key insights that reflect 'Advances in Computer and Computational Sciences' from upcoming researchers and leading academics around the globe. It gathers high-quality, peer-reviewed papers presented at the International Conference on Computer, Communication and Computational Sciences (IC4S 2018), which was held on 20-21 October, 2018 in Bangkok. The book covers a broad range of topics, including intelligent hardware and software design, advanced communications, intelligent computing techniques, intelligent image processing, and web and informatics. Its goal is to familiarize readers from the computer industry and academia with the latest advances in next-generation computer and communication technology, which they can subsequently integrate into real-world applications.